HAMBATAN KOMUNIKASI DALAM ORGANISASI IKATAN MAHASISWA BERPRESTASI WONOGIRI - Adham Helian Wicaksana; wiwid Noor Rakhmad; Sri Budi Lestari (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
Communication is an important thing that must work well and be as effective as possible in organizations, including the Ikatan Mahasiswa Berprestasi (IMAPRES) Wonogiri. This research was motivated by the participation of IMAPRES members who were not optimal, where most members had to be evaluated because of the lack of innovation that occurred. This study aims to determine communication barriers that occur in the IMAPRES organization and to find out the steps taken by the IMAPRES organization in solving communication barriers, using a qualitative descriptive study type method. This study uses a positivistic paradigm with the data collection technique used is in-depth interviews. The theory used in this study is organizational information theory and neoclassical or human relations theory. The results of this study indicate that the IMAPRES Wonogiri has various kinds of communication barriers due to the distance factor, starting from physical distance, social distance, and psychological distance that occurs among members of the Wonogiri IMAPRES. Communication barriers that occur such as ineffectiveness of members in utilizing existing communication media, separation of members based on campus area, existence of friendship circles based on place of education and views of administrators, jealousy over positions, differences in work pressure, unequal perceptions of high idealism, and personal problems brought into the organization. This study also found that the level of participation of IMAPRES members tends to be maximal in the form of time and material contributions, while contributions in the form of energy and thoughts are still minimal. Then there have been efforts made by IMAPRES Wonogiri in resolving communication barriers that occurred including by personally confirming, creating a Google form link, requiring oncam in online forums, holding reshuffles, holding evaluation forums, and providing mediators.